2015
DOI: 10.1155/2015/641601
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Stall Inception Mechanisms of Low Speed Contra Rotating Axial Flow Fan Stage

Abstract: The present paper is an attempt in understanding the stall inception mechanism in a low speed, contra rotating axial flow fan stage, using wavelet transforms. The rotors used in this study have relatively large tip gap (about 3% of the blade span) and aspect ratio of 3. The study was carried out near stall and at stall mass flow conditions for different speed ratios of rotor-2 to rotor-1. Unsteady pressure data from the casing wall mounted sensors are used to understand the stall inception mechanism. The wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…They were able to predict the stall using the transition of the second harmonic signal obtained from the frequency analyses. Tegegn and Pradeep 16 analysed the unsteady casing static pressure measurements using wavelet transforms to understand the stall inception mechanism in a high-aspect ratio contra-rotating fan stage. Stall inception was observed to occur through LLSDs for both rotors.…”
Section: Introductionmentioning
confidence: 99%
“…They were able to predict the stall using the transition of the second harmonic signal obtained from the frequency analyses. Tegegn and Pradeep 16 analysed the unsteady casing static pressure measurements using wavelet transforms to understand the stall inception mechanism in a high-aspect ratio contra-rotating fan stage. Stall inception was observed to occur through LLSDs for both rotors.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is referred to as "stall" caused by an increase in incidence angle due to a decrease in flow rate. When an axial fan enters the stall region during operation, significant energy loss, vibration, and noise are generally caused [37,38]; thus, at least at the designed flow rate, the stall region should be avoided from the viewpoint of saving energy and increasing lifetime for an axial fan. The axial fan of this study was not related to the stall region near the design flow rate.…”
Section: Validation For Numerical Analysismentioning
confidence: 99%
“…3,4 Rotor speed ratio, rotor stagger, axial spacing between the rotors, tip clearance, and solidity are the most important parameters on the performance of contra-rotating fans. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In the investigation performed by Nouri et al 4 and Mistry and Pradeep, 6 the effect of axial gap between rotors is studied. Results reveal that this parameter does not affect the fan performance considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Flow instabilities in contra-rotating fans have been studied numerically and experimentally by a number of researchers. [7][8][9][10][11][12][13] Dejene Toge and Pradeep 8 studied the stall inception of a low-speed contra-rotating fan, experimentally. It was shown that the rear rotor was critical and limited the fan operability.…”
Section: Introductionmentioning
confidence: 99%